Being an athlete and being a young person: Technologies of the self in managing an athletic career in youth ice hockey in Finland - Ojala, A.-L. (International Review for the Sociology of Sport, 2020)
Engaging in youth sports is a major investment, and it requires choosing and balancing between an athlete`s life and other practices and ways of life important to adolescents. In this Foucauldian year-long ethnographic study on Finnish 18-20-year-old elite male ice hockey players I consider an athletic career as a moral question and examine what aspects of their behaviour are affected when these players submit to the external and internal control they encounter when advancing themselves and their careers, and how they problematize the codes that govern their actions. The players expressed six modes of subjection altogether that were important to cultivation of the self: exercising, nutrition, rest, motivation, player role and emotions. The processes of cultivation were strongly guided by coaches and well internalized by the players. However, the hockey players were also young people with interests and choices quite different from a disciplined athletic life, and the coaches also helped in the construction of these spheres. I propose in this study that these spheres may be important in managing the training load and the career pressure that athletes necessarily face during the `investment years` (15+) in sport.